Synthesis of Chiral N-Nitro-oxazolidin-2-ones and O-(β-Nitraminoalkyl) Carbamates in Liquefied 1,1,1,2-Tetrafluoroethane Medium - Arabadzhi, Svetlana S.; Zharkov, Mikhail N.; Kuchurov, Ilya V.; Zlotin, Sergei G. (Synthesis, 2020)
A convenient synthesis of chiral N-nitro-oxazolidin-2-ones by nitration of α-amino acid derived 1,3-oxazolidin-2-ones containing one or two stereogenic centers with dinitrogen pentoxide in liquefied 1,1,1,2-tetrafluoroethane medium has been developed. The obtained N-nitroheterocycles were converted into enantiomerically pure O-(β-nitraminoalkyl) carbamates by treatment with ammonia or amines in the same solvent. The synthesized N-nitro compounds are slightly toxic in vitro to Human Embryonic Kidney 293 (HEK293) cells.
Keywords: nitration; dinitrogen pentoxide; N-nitro-oxazolidin-2-ones; primary nitramines; 1,1,1,2-tetrafluoroethane